PENGARUH TEKANAN ANGGARAN WAKTU, KOMPLEKSITAS TUGAS, LOCUS OF CONTROL, DAN ETIKA PROFESI TERHADAP PERILAKU DISFUNGSIONAL AUDIT: THE EFFECT OF TIME BUDGET PRESSURE, TASK COMPLEXITY, LOCUS OF CONTROL, AND PROFESSIONAL ETHICS ON DYSFUNCTIONAL AUDIT BEHAVIOR - Rohani Libra Siagian; Mukhlasin Mukhlasin; Reskino Reskino; Renato Sitompul (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
In auditing, an auditor must always be guided by audit standards to maintain the quality of the audit results so they can be free from material misstatement. However, internal and external environmental factors may lead auditors to deviant behavior. Thus, this study examines the effect of time budget pressure, task complexity, locus of control, and professional ethics on dysfunctional audit behavior. The survey method was used for 40 respondents of BPK RI Representative of DKI Jakarta auditors through a questionnaire instrument with a convenience sampling approach. Data analysis uses ordinary least squares (OLS) in testing the four hypotheses proposed. The results showed that locus of control and task complexity positively affected dysfunctional audit behavior. Meanwhile, professional ethics has a negative effect on audit dysfunctional behavior. In addition, the results also show that time budget pressure does not affect dysfunctional audit behavior. The overall research results indicate that there is a need to re-evaluate the time and budgetary pressures of audit implementation by BPK personnel to mitigate the potential for deviant behavior.